2005
DOI: 10.1016/j.actamat.2005.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic prediction of thixoformability in alloys based on the Al–Si–Cu and Al–Si–Cu–Mg systems

Abstract: Most commercial semi-solid processing (of which thixoforming is one type) utilises the conventional casting alloys A356 and A357. There is, however, a demand to widen the range of alloys, including those with higher performance which tend to show poor characteristics for thixoforming. Thermodynamic calculation packages, such as MTDATA, provide a tool for predicting thixoformability. Here, the effects of compositional variations, in particular the effect of added copper on the thixoformability of alloy A356 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1
19

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(95 citation statements)
references
References 15 publications
1
74
1
19
Order By: Relevance
“…Atkinson et al [6] identified that it is the slope of the liquid fraction versus temperature curve in the region of 30-50% liquid which is the key parameter. More recently, Liu et al [7] using the MTDATA thermodynamic package and DSC predicted the liquid fraction sensitivity ( / ) =0.4 at 40% fraction liquid (mid-way through the process range of 30-50% liquid) and argued that it should not change too rapidly with temperature in the process window.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atkinson et al [6] identified that it is the slope of the liquid fraction versus temperature curve in the region of 30-50% liquid which is the key parameter. More recently, Liu et al [7] using the MTDATA thermodynamic package and DSC predicted the liquid fraction sensitivity ( / ) =0.4 at 40% fraction liquid (mid-way through the process range of 30-50% liquid) and argued that it should not change too rapidly with temperature in the process window.…”
Section: Introductionmentioning
confidence: 99%
“…Atkinson et al [6] identified that it is the slope of the liquid fraction versus temperature curve in the region of 30-50% liquid which is the key parameter. More recently, Liu et al [7] using the MTDATA thermodynamic package and DSC predicted the liquid fraction sensitivity ( / ) =0.4 at 40% fraction liquid (mid-way through the process range of 30-50% liquid) and argued that it should not change too rapidly with temperature in the process window.As pure metals and the eutectic alloys do not have a freezing (or melting) range, it has been conventionally expected that it is not possible for them to be semi-solid processed because ( / ) is ∞. Based on Liu et al 's theory [7], recent studies have been focused on the evaluation the thixoformability through processing temperature and modifying alloy elements [8][9][10].…”
mentioning
confidence: 99%
“…The composition of ADC10 alloy, which is close to the eutectic, does not seem responsive to the thermodynamic criterion for semi-solid processing. 14,15) The criterion is based on the temperature sensitivity of the solid fraction (df S /dTϽ0.015) and the solidification range (10°CϽTϽ150°C), which are important factors for the alloy selection. Figure 1 shows the solid fraction/temperature relationship of ADC10 alloy, as calculated using Thermo-Calc.…”
Section: Methodsmentioning
confidence: 99%
“…12,27 They are selected based on the wide solidus-liquidus temperature range in aluminium, [28][29][30][31][32][33][34][35] magnesium 12,36,37 alloys and steels, [38][39][40][41][42][43][44] and the examples are given in Table 1. New approach assumes that the chemical composition of alloys for SSM should be designed so that they meet specific thermodynamic, microstructural, and processing requirements.…”
Section: Designing New Alloys For Ssm and Postprocessing Heat Treatmentmentioning
confidence: 99%